The Test of word-finding abilities in children (gujarati) - K.G, Javer Gala (Journal of All India Institute of Speech and Hearing)
The Test of Word Finding Abilities in Children (Gujarati) (TWAC -G) is based on the diagnostic model which employs naming sections, incorporates indices traditionally used to define word finding problems in adults and children and provides for a comprehension assessment of target word naming errors. The test was administered to 40 normal, Gujarati speaking children of primary grades. Age ranged from 5-9 years.